Two Countries, One Mission: Comparing Member of Ottoman and English Pay-to-Pray Institutions (XVI and XVII. Centuries) - Songül Şenlik (Belleten)
This article compares paid prayer workers employed in the Ottoman Empire and England during the sixteenth and seventeenth centuries. Throughout history, clergy in all societies undertook the duty of offering prayers. However, English and Ottoman pay-to-pray workers were specifically obligated to pray for the souls of those who provided them with dedicated income. These individuals were often in need of state protection and care and were in need of support and assistance. Using studies conducted on paid prayer workers and documents from Ottoman archives, this article seeks to identify the similarities and differences between the prayer workers of these two countries. The article argues that the similarities were shaped by the requirements of religion and social life, while the differences were shaped by the economic and cultural conditions of the time. Following a brief introduction to prayer workers, the article highlights the working conditions, qualifications, responsibilities, and income of those who received a salary or, for various reasons, acquired income and thus prayed for the state, the ruler, and the income provider. Due to the lack of in-depth studies on the topic and the absence of detailed publications on such prayer workers in both states, this article is of an essay.